Jogos eletrônicos e cultura mediada por computadores: paradoxos culturais e organizacionais advindos das inovações em tecnologias de informação - Takeyoshi Imasato; Zilá Pedroso Mesquita (Ciências Sociais Unisinos)
Information technologies and microelectronics, through personal computers, Internet, email, among others tools, are undeniably creating changes in the dynamics of social relations and consequently modifying cultural elements of contemporary society. On the other hand we are confronted with an old fact of our civilization that still persists: war. This article discusses a situation where these two sets of historical events come together. By presenting a case study of a community formed by Brazilians called Brazilian Power, people who gather to play America¿s Army, an electronic game created by the United States Army, this article analyzes and tries to understand the culture of this organization and to disclose some of the cultural paradoxes resulting from new information technologies.